2018
DOI: 10.2478/jas-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Israeli Acute Paralysis Virus (IAPV) and Apis mellifera Filamentous Virus (AmFV) in Honey Bees in Mexico

Abstract: The recent alarming loss of honey bee colonies around the world is believed to be related to the presence of viruses. The aim of this study was to detect two major viral diseases, Apis mellifera Filamentous virus (AmFV) and Israeli Acute Paralysis Virus (IAPV) using Reverse Transcription - Polymerase Chain Reaction RT-PCR, in honey bees in Mexico. Adult and larvae honey bee samples were collected from asymptomatic colonies of six major beekeeping regions in the state of Chihuahua, Mexico. Both viruses were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A few previous studies had reported the presence of DWV in localities within the states of Chihuahua in the North, Nayarit in the Pacific Coast, and the Federal District in the High Plateau region [28][29][30]68], although its prevalence and intensity were not determined. More recently, a study conducted in the state of Jalisco reported the frequency and levels of V. destructor and DWV in honey bee colonies of African or European descent [69].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A few previous studies had reported the presence of DWV in localities within the states of Chihuahua in the North, Nayarit in the Pacific Coast, and the Federal District in the High Plateau region [28][29][30]68], although its prevalence and intensity were not determined. More recently, a study conducted in the state of Jalisco reported the frequency and levels of V. destructor and DWV in honey bee colonies of African or European descent [69].…”
Section: Discussionmentioning
confidence: 97%
“…Another common virus found in brood and adult honey bees is the sacbrood bee virus (SBV), which does not seem to pose a major threat to honey bee health. In Mexico, the presence of DWV, ABPV, IAPV, KBV, and SBV has been reported and confirmed by molecular analyses, but only in some states or localities of the country [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were RT-PCR analyzed to detect DWV, BQCV, IAPV, and CBPV. These viruses had been previously reported to exist in Mexico [ 47 , 48 , 49 , 50 ]. Total RNA was extracted with TRIzol ® reagent (Fisher Scientific, Mississauga, ON, Canada) from three bees per sample following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In Israel, IAPV was isolated from dead honey bees, and the characterization of the virus showed that there was a high similarity between this virus and the Kashmir bee virus and ABPV [7]. There are also several reports characterizing IAPV in other countries [10][11][12][13]. Moreover, the results of studies show that IAPV causes a permanent infection at all growth stages and in different honey bee species.…”
Section: Introductionmentioning
confidence: 99%